2019
DOI: 10.3892/ol.2019.9952
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed genes ASPN, COL1A1, FN1, VCAN and MUC5AC are potential prognostic biomarkers for gastric cancer

Abstract: Gastric cancer (GC) is one of the most common malignancies worldwide. To the best of our knowledge, no biomarkers have been widely accepted for the early diagnosis and prognostic prediction of GC. This study aimed to identify potential novel prognostic biomarkers for GC. The dataset GSE29272, which originates from the public database Gene Expression Omnibus, was employed in the present study. The online tool GEO2R was used to calculate the differentially expressed genes (DEGs) in GSE29272 between tumour tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 56 publications
6
60
0
Order By: Relevance
“…A strong correlation of elevated ECM expression and poor prognosis was also found in luminal BCa (Riaz et al, 2012). In pediatric osteosarcoma, a signature of high ECM turnover was found to be highly prognostic for chemoresistance (Mintz et al, 2005) and, in gastric cancer expression of a signature containing Col1a1, Fn1, and Muc5a, was highly predictive of overall and diseasefree survival (Jiang et al, 2019). Besides indicators for immune suppression, high expression of collagens Col3a1, Col4a1, and Col5a2 is correlated with poor prognosis in glioblastoma .…”
Section: Ecm Profiles As Prognostic Markersmentioning
confidence: 77%
“…A strong correlation of elevated ECM expression and poor prognosis was also found in luminal BCa (Riaz et al, 2012). In pediatric osteosarcoma, a signature of high ECM turnover was found to be highly prognostic for chemoresistance (Mintz et al, 2005) and, in gastric cancer expression of a signature containing Col1a1, Fn1, and Muc5a, was highly predictive of overall and diseasefree survival (Jiang et al, 2019). Besides indicators for immune suppression, high expression of collagens Col3a1, Col4a1, and Col5a2 is correlated with poor prognosis in glioblastoma .…”
Section: Ecm Profiles As Prognostic Markersmentioning
confidence: 77%
“…MUC5AC is a wellknown marker of gastric differentiation, which is considered to be a very important prognostic indicator of GC and is often used in clinical evaluation [27][28][29]. It has been found that the expression of MUC5AC in stomach decreases with the development of intestinal metaplasia, and the expression of MUC5AC is related to tumor stage: the expression level of MUC5AC in advanced GC is lower than that in early GC [30]. This is consistent with our analysis results that the expression of MUC5AC in normal tissues is higher than that in GC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted a number of genes associated with GC. [24][25][26] The specific molecular mechanisms governing this disease, however, are complex, and as such further data mining efforts are needed to identify relevant candidate biomarkers for GC diagnosis.…”
Section: Discussionmentioning
confidence: 99%